2022
DOI: 10.3390/land11010133
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anaerobic Digestate on the Soil Organic Carbon and Humified Carbon Fractions in Different Land-Use Systems in Lithuania

Abstract: The most important component of agricultural system are soils as the basis for the growth of plants, accumulation of water, plant nutrients and organic matter. The main task of our research was to ascertain changes in soil organic carbon (SOC) and mobile humified carbon fractions in digestate-treated soils. We have performed three field experiments using the same design on two soil types in 2019–2020. We studied the fertilization effects of different phases of digestate on Retisol and Fluvisol. Fertilization t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The composting of digestate requires the proper adjustment of the C/N ratio by the addition of lignocellulosic waste which has the function of bulking agent, which also increases the aromatic-C in the final compost [ 19 ]. Moreover, the organic matter fraction of digestate contains a more recalcitrant fraction of OM from the OFMSW, due to the mineralization occurring during the anaerobic process, which leads to a higher fraction of easily degradable compounds consumption [ 35 , 36 ]. For both the previous reasons, the compost from digestate may be considered different from the compost from raw OFMSW.…”
Section: Discussionmentioning
confidence: 99%
“…The composting of digestate requires the proper adjustment of the C/N ratio by the addition of lignocellulosic waste which has the function of bulking agent, which also increases the aromatic-C in the final compost [ 19 ]. Moreover, the organic matter fraction of digestate contains a more recalcitrant fraction of OM from the OFMSW, due to the mineralization occurring during the anaerobic process, which leads to a higher fraction of easily degradable compounds consumption [ 35 , 36 ]. For both the previous reasons, the compost from digestate may be considered different from the compost from raw OFMSW.…”
Section: Discussionmentioning
confidence: 99%
“…Since AD was developed for energy production, the potential use of digestate as exogenous organic matter (EOM) to enhance soil carbon sequestration is still being evaluated. However, the importance of the role of carbon mitigation in current and future EU policies on agricultural systems increases the significance of digestate as a potential contributor to SOC formation (and carbon dynamics) [8,9]. Several studies have concluded that digested EOM shows higher stability than undigested EOM in SOM [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The use of liquid digestate fraction, generally richer in LOC, was strongly encouraged by some authors [22,27]. On the other hand, its contribution to SOC stock is still weak compared to solid fraction digestate, due to low carbon input [9,22]. Because digestate based on food waste has properties close to those of the liquid fraction of digestate from agricultural waste, e.g., raw material with lower C:N ratio and low dry biomass of the final product, we had to assume lower recalcitrance of the digestate fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Biogas reactors (BRs) are designed to produce methane from organic waste by anaerobic digestion (AD). BR produce leftovers, also known as digestate that has been successfully used as biofertilizer due to their high contents of mineralized Nitrogen (N), Phosphorus (P), Potassium (K), and organic materials [1]. Recycling organic materials to land is considered the best practicable environmental option in most circumstances, completing both natural nutrient and carbon cycles.…”
Section: Introductionmentioning
confidence: 99%